Larangan Membaca Al-Qur’an Bagi Wanita Haid Penghafal Al-Qur’an: Studi Takhrij dan Syarah Hadis - M Yusuf Hilmi Fithori; Muhamad Yoga Firdaus; Saifudin Nur (Gunung Djati Conference Series, 2022)
This study aims to analyze and explain the hadith about menstruating women memorizing the Qur'an. This study uses a qualitative method that focuses on literature study with takhrij and syarah hadith approaches. This research and discussion show that the hadith of Imam At-Tirmidhi number 121 has mua'anan quality, so it cannot be used as an Islamic argument because the chain of this hadith has one narrator is weak. The syarah of this hadith explains the prohibition of menstruating women and junub from reading the Qur'an. However, it is permissible to read only one letter, and at the end of the verse, it is advisable to read tasbih and tahlil, because this hadith has a weak chain. It is permissible according to the four schools of thought to read the Qur'an. An 'a for menstruating women or people with small or large hadads to read the Qur'an as long as they do not touch it. As for women who are allowed to interact with the Qur'an on the condition that they are a memorizer of the Qur'an, a teacher of the Qur'an, and are repeating the memorization of the Qur'an.